Der inspizierte Muslim: Zur Politisierung der Islamforschung in Europa - Amir-Moazami, Schirin (transcript, 2018)
Muslims in Europe are in the public focus. They are eyed, examined and surveyed. Academic research makes up part of this concentrated public and political interest. The book pauses at this point and poses the question: Who is viewed as a Muslim in what way? By whom and why? Which issues are formative, and what epistemological and normative assumptions are they based on? The contributions featured in this volume illuminate the connections between academic knowledge and political intervention with a (self-)critical eye. For it is not an increase in knowledge about Muslims but rather a critical reflection about the preconditions of the production of knowledge that will lead to an effective critique of its emerging discourse.